Embryotoxic and Teratogenic Effects of Norfloxacin in Pregnant Female Albino Rats - Mohamed Aboubakr; Mohamed Elbadawy; Ahmed Soliman; Mohamed El-Hewaity (Advances in Pharmacological Sciences)
This study was designed to investigate the possible developmental teratogenicity of norfloxacin in rats. Forty pregnant female rats were divided into four equal groups. Group A received norfloxacin in a dose of 500 mg/kg·b·wt/day orally from 6th to 15th day of gestation. Groups B and C received 1000 and 2000 mg/kg·b·wt/day orally for the same period, respectively; Group D behaved as control and received 0.5 mL distilled water orally for the same period. The dams were killed on 20th day of gestation and their fetuses were subjected to morphological, visceral, and skeletal examinations. Norfloxacin significantly decreased the number of viable fetuses, increased the number of resorbed fetuses, and induced retardation in growth of viable fetuses; some visceral and skeletal defects in these fetuses were seen and these effects were dose dependant. Conclusively, norfloxacin caused some fetal defects and abnormalities, so it is advisable to avoid using this drug during pregnancy.